Green HRM, Inclusive Leadership, And Job Satisfaction as Predictors of Innovative Behavior in The 4-Star Hospitality Sector - Tiarapuspa; Fadel A’la An Nasher; Desty Survia (Indonesian Management and Accounting Research, 2024)
The aim of this research is to analyze Green HRM, job satisfaction, inclusive leadership, innovative behavior, among hotel industry employees in Bandar Lampung. This research is supported by secondary data in the form of information from each journal processed using SPSS Amos version 22. This research uses purposive sampling. The expected results in this research are concluded as follows; the results of descriptive statistical research for the Green HRM variable obtained an average total value of 4.43, the results of descriptive statistical research for the Inclusive Leadership variable obtained an average total value of 4.42, the results of descriptive statistical research for The Innovative Behavior variable obtained a total average value of 4.44. The results of descriptive statistical research for the Job Satisfaction variable obtained a total average value of 4.39. This figure shows that four-star hotel employees in Bandar Lampung are satisfied with their work. Keywords: Green HRM, Job Satisfaction, Inclusive Leadership, Innovative Behavior